ADSORPTION MECHANISM AND STRUCTURAL INVESTIGATION OF DOPED C60 FULLERENES WİTH PENTYLAMINE - Metin Bilge (Anadolu University Journal of Science and Technology. A : Applied Sciences and Engineering, 2017)
Interaction mechanisms of doped fullerenes and various types of molecules have been paid increasing attention. In this research, absorption mechanism, structural and electronic properties, natural bond orbital analysis between pentylamine (pa) and doped (Si or Al) C60 fullerenes were investigated by quantum mechanical calculations. Bond order and binding energy results suggest that a chemisorption occur between nitrogen atom of pa and silicon/aluminum atoms of fullerene cages, examined complexes yielded with higher binding energy in water media and the system of AlC59…pa in water was found as having the highest binding energy.